Efficacy differences of Queen’s crepe-myrtle (Lagerstroemia speciosa) and aloe vera extract on the interleukin-6 and osteoblast levels in the healing process of alveolar osteitis - Bernadi, Willy; Hardianto, Andri; Yuza, Abel Tasman; Harlina, Eva (Padjadjaran Journal of Dentistry, 2021)
Introduction: Alveolar osteitis is the most common complication after tooth extraction, which occurs 2 to 4 days after and causes disruption of wound healing. Pucuk Bungur/Queen’s crepe myrtle  (Lagerstroemia speciosa) and aloe vera have biological and pharmacological benefits in experimental animals: antimicrobial, anti-inflammatory, and antioxidant. They also affect the wound healing process.  These benefits are a good combination as an alternative remedy for alveolar osteitis treatment. This study was aimed to analyse the effect of Lagerstroemia speciosa compared to aloe vera extracts gel on the wound healing process after tooth extraction in Sprague-Dawley mice with alveolar osteitis. Methods:  This research was an experimental laboratory. Twenty-seven Sprague-Dawley mice were randomly divided into three groups. The first group was the osteitis (control) group treated with 1:1000 adrenaline insertion for 1 minute on the left maxillary first molars socket; the second group was the osteitis group administered with the application of Lagerstroemia speciosa, and the third group was the osteitis group administered with the application of aloe vera gel. Normal mice in the control group were not given any treatment, only osteitis mice. The interleukin-6 level was examined after, and the number of osteoblasts was also calculated on the 3rd, 5th and 14th day after the necropsy was performed. Data were analysed with one-way ANOVA to compare the effectiveness of wound healing of alveolar osteitis in each group. Results: From the data analysis, the osteitis group applied with  Lagerstroemia speciosa gel had good activity in the inflammation phase of the healing process of alveolar osteitis compared to other groups. Conclusion: Lagerstroemia speciosa can be a potential alternative treatment to reduce inflammation and accelerate the healing of osteitis because it shortens the inflammatory phase and accelerates collagen production in wound healing.